Data for: Sleep interventions for children and adolescents: a systematic literature review of effectiveness and cost-effectiveness - Johansson, Pia (Halmstad University, 2024)
The data material illustrates the systematic literature review process, containing all the supporting material, tools, and summaries employed during the work, and that is not reported in detail in the scientific publications. The READ ME-document contains some explanations to the material.
The review concerned sleep interventions among children, in the general population and in children with ADHD, that are reported in one scientific article each. The review investigated effectiveness of the interventions as well as cost-effectiveness, from international peer-reviewed scientific studies deemed relevant for a Swedish context.

Datamaterialet visar processen i den systematiska litteraturgenomgången, och innehåller allt underlagsmaterial, verktyg och sammanfattningar som använts i arbetet, men som inte redovisats i detalj i de vetenskapliga publikationerna. READ ME-dokumentet innehåller vissa förklaringar till material. Se den engelska versionen för mer detaljer.
Data för: Insatser för förbättrad sömn hos barn och unga: en systematisk litteraturgenomgång över effektivitet och kostnadseffektivitet
Keywords: CHILDREN; BARN; SLEEP; SÖMN; SLEEP DISORDERS; SÖMNSTÖRNINGAR; PHYSIOLOGICAL EFFECTS; FYSIOLOGISKA EFFEKTER; ADOLESCENTS; UNGDOMAR; Costs and Cost Analysis; Kostnader och kostnadsanalys; Efficiency; Effektivitet; Systematic Reviews as Topic; Systematiska översikter som ämne; Adolescent Health; Ungdomars hälsa; CHILD HEALTH; BARNS HÄLSA; Medication and treatment; Medicinering och behandlingar; Specific diseases, disorders and medical conditions; Specifika sjukdomar, störningar och medicinska tillstånd; Youth; Ungdomar; Children; Barn; Pediatrics; Pediatrik